CIRCULATION OF ANTIPHOSPHOLIPID ANTIBODIES AND IVF FAILURES - N. S. Stuleva; D. K. Khizroeva; T. Y. Mashkova; G. R. Abramyan (Акушерство, гинекология и репродукция, 2016)
The antiphospholipid antibodies (APA) exert multiple effects on the hemostasis system causing damage to all of its protective components including the endothelial barrier, natural anticoagulant function and endogenous fibrinolysis and activating the platelet of hemostasis, which is associated with numerous obstetrical complications and infertility. Objective. This study aimed at elucidating the effect of the presence of APA on the outcomes of assisted reproductive technology (ART). Materials and Methods. A total of 217 women diagnosed with infertility and planning to get pregnant using the assisted reproductive technology (ART) have been examined. Results. The results of examination demonstrated a high prevalence of circulating APA in a group of women underwent IVF failure. Conclusion. The thrombophilia can be one of the reasons of failures of in-vitro fertilization.